ON HYPER PSEUDO MV-ALGEBRAS - Borzooei, R.A.; Zahiri, O. (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, we introduce the notion of hyper pseudo MV-algebra as a generalization of pseudo MV-algebra and hyper MV-algebra. Then we investigate some properties of this structure and attempt to construct a hyper pseudo MV-algebra from a l-group. Finally, we proved some theorems about filters, ideals, congruence relations, in hyper pseudo MV-algebras.